The Short-term Influence of a Mediterranean-type Diet and Mild Exercise with and without Red Wine on Patients with the Metabolic Syndrome - van Velden, D.P.; van der Merwe, S.; Fourie, E.; Kidd, M.; Blackhurst, D.M.; Kotze, M.J.; Mansvelt, E.P.G. (South African Journal of Enology and Viticulture, 2016)
The metabolic syndrome is a target for the dietary prevention of cardiovascular disease. The effect of adding red wine to the diet has not been fully investigated. This study examined whether a Mediterranean-type diet complemented with red wine and mild exercise had an impact on patients with the metabolic syndrome in the short term. Twelve patients with the metabolic syndrome consumed a Mediterranean-type diet for four weeks without and with red wine respectively and performed mild exercise. We implemented the diagnostic criteria for the metabolic syndrome as formulated by the Adult Treatment Panel III (ATP III) in 2001. The patients were also screened for multiple genetic markers implicated in cardiovascular disease. Weight, body mass index, abdominal circumference and blood pressure were measured, as well as various biochemical, haematological and inflammatory markers. There was a significant decrease in the body weight (p = 0.04) and an increase in ORAC value (p = 0.035) after the dietary intervention. A significant decrease in systolic blood pressure (p = 0.045) was observed. Red wine had no additional benefits. Although diet reduced weight and blood pressure, the lipoprotein and pro-coagulant profiles of patients with the metabolic syndrome were not affected in this study. These findings may be explained partly by the diverse genetic profile identified among the study participants, as 50% had mutations involved in lipid metabolism that may influence the response to dietary intervention and alcohol consumption.